The effect of a modified zeolite additive as a cement and concrete improver - Ikotun, Bolanle Deborah (My University, 2010)
This dissertation presents a study that investigated the potential of a modified zeolite additive known as PowerCem to improve the properties of cement mortar and concrete. Improvement of the characteristics of cement mortars and concrete is of interest to various researchers and practitioners in the field of construction materials engineering. The product, a blend of selected alkaloids and zeolite, is commercially available and effectively used in soil stabilization for road construction. However, its influence and effectiveness on the properties of cementitious systems has not been explored. The emphasis of this study was on improvement of the strength and durability properties of cement mortar and concrete using PowerCem (PWC) additive. Tests carried out on mortar samples include flow, flexural strength, compressive strength, oxygen permeability, sorptivity, porosity, resistance to sulphate attack, and resistance to alkali silica reaction. Tests carried out on concrete samples include workability, split tensile strength, compressive strength, oxygen permeability, sorptivity, porosity, and carbonation. The hydration behaviour of sample pastes were observed using differential thermal analysis (DTA) and thermogravimetric analysis (TGA). Improvement of strength and durability properties of cement mortar and concrete was observed when PWC additive was used at optimum proportions. In conclusion, PWC additive showed the potential to effectively improve mortar, concrete strength and durability properties when used at optimum proportions between 0.4 % and 0.6 %.